HADIS SEBAGAI SUMBER PENDIDIKAN AKHLAK DAN PENDIDIKAN SOSIAL - Maslani Maslani; Agnes Nuraeni Muslim; Anisa Fitriany Sholehah; Deden Sofwan Ismail; Gunawan Gunawan; Sandi Aditya Nugraha; Usman Usman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Moral education in Islam is education that originates from local religious and cultural teachings and aims to create peace, tranquility and peace in life. In Islamic teachings, the term hablum min annas is known which refers to fostering good relationships with humans. This is one of the goals of moral education, namely to enable humans to relate to and do good to other people. Because we must always be social creatures who need other people. The hadith clearly shows that Rasulullah SAW really liked people with noble character and did not like people who talked a lot. Apart from that, another hadith also explains that we are commanded to love others as we love ourselves Alone. Manifesting this feeling of love is by helping each other and providing benefits to others. This feeling of love is conveyed to others by putting aside existing differences so that divisions do not arise.